Uji Coba Pendampingan Pembukuan UMKM Menggunakan Si Apik dan MYOB - Biswan, Ali Tafriji; Januwardhani, Filistea Glory Chantika; Perdana Putra, Hardana Gading; Fahlevi, Muhammad Rizah; Negari, Muthi’a Sekhar (Journal Pemberdayaan Masyarakat Indonesia, 2024)
Not only beneficial for students, accounting practice should make a real contribution to the business world industry world (DUDI). A real contribution to DUDI can be realized in the form of a social project for bookkeeping transactions for micro, small and medium enterprises (MSMEs), in this case the Big Sport Shoe Store. This project aims to help make it easier for MSMEs to record their business transactions using relatively practical tools. In this project, the team assists MSMEs in recording transactions using two devices, namely Si Apik and MYOB. The result of this project is that there is a tendency for MSMEs to choose Si Apik over MYOB because of the practicality and appearance of the application. Si Apik is more suitable for micro, small and medium businesses, while MYOB is more suitable for medium to large business units with a wider variety of transactions, including accommodating taxation.